Pengembangan Platform E-Commerce Berbasis OpenCart untuk Industri Kreatif UMKM Kerajinan Rajut di Kabupaten Pasaman Barat - Hasnah, Radiatul; Annas, Firdaus; Sartiva, Yola (JOVISHE : Journal of Visionary Sharia Economy, 2023)
This research is motivated by how to develop an opencart-based e-commerce platform for the creative industry of knitting craft MSMEs in West Pasaman district. The purpose of this research is to design and build an opencart-based e-commerce platform that suits the needs of creative industry players of knitting craft MSMEs in West Pasaman district. Making it easier for knitting craft MSME players to market their products online to reach a wider market and facilitate the process of product management, transactions, and communication between businesses and customers through the integration of e-commerce technology. The method used in this research is Research and Development (R&D), which was chosen because it can develop an OpenCart-based e-commerce platform according to the needs and characteristics of the creative industry of knitting craft MSMEs in West Pasaman Regency. The R&D process goes through several stages, starting from needs analysis, platform design, implementation, and testing. This approach aims to produce products that can be directly used by MSME players, providing practical solutions to their product marketing problems. The R&D method also enables the identification, design, and testing of systems that can improve the competitiveness and business effectiveness of knitting craft MSMEs through the utilization of digital platforms. The findings of this research are that the development of an OpenCart-based e-commerce platform for the creative industry of knitting craft MSMEs in West Pasaman Regency has succeeded in improving market access and product competitiveness. This platform makes it easier for MSME players to market their products digitally, expand market reach, and increase sales. In addition, MSME players also gained a better understanding of the use of technology in their business. Therefore, this e-commerce platform has made a significant contribution to the development of the local economy and creative industry in the area.